2019
DOI: 10.3168/jds.2019-16272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding synthetic zeolite A during the prepartum period on serum mineral concentration, oxidant status, and performance of multiparous Holstein cows

Abstract: The objective of this study was to determine the effects of feeding synthetic zeolite A for 3 wk before expected calving on peripartal serum mineral concentrations, hypocalcemia, oxidant status, and performance. Holstein cows (n = 55) entering their second or greater lactations were assigned randomly to 1 of 2 dietary treatments starting 21 d before expected calving: control (CON: 40% corn silage, 33% wheat straw, and 27% concentrate; n = 29) or experimental [EXP: CON plus zeolite A (X-Zelit, Protekta Inc., Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 46 publications
4
26
0
2
Order By: Relevance
“…The current study has showed that oral supplementation with 150 g/day of organically modified clinoptilolite improved colostrum quality. Although results of several research groups showed a beneficial effect of zeolite supplementation, the results are difficult to compare directly (Papaioannou et al ., 2005; Kerwin et al ., 2019). It has been reported that the extent of performance enhancement effects is related to the types of zeolite, their physico-chemical properties, purity in terms of the content of clinoptilolite, as well as to the supplementation level used in the diets (Papaioannou et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study has showed that oral supplementation with 150 g/day of organically modified clinoptilolite improved colostrum quality. Although results of several research groups showed a beneficial effect of zeolite supplementation, the results are difficult to compare directly (Papaioannou et al ., 2005; Kerwin et al ., 2019). It has been reported that the extent of performance enhancement effects is related to the types of zeolite, their physico-chemical properties, purity in terms of the content of clinoptilolite, as well as to the supplementation level used in the diets (Papaioannou et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the particle size of the zeolitic material, crystallite size and the degree of aggregation, as well as the porosity of individual particles strongly affect its ion exchange, adsorption and catalytic properties (Papaioannou et al ., 2005). In a recent study it was shown that the use of synthetic zeolite A in the prepartum period of cows in second and greater lactation did not influence colostral IgG concentration and IgG mass (Kerwin et al ., 2019). According to data reviewed in Papaioannou et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeolite A binds Ca, P i , and Mg in the rumen and thus creates a diet low in Ca (Thilsing et al, 2006). Recent studies have shown that cows fed zeolite A for 2 to 3 wk prepartum have increased serum Ca concentrations during the immediate peripartum period, but none reported differences in postpartum performance (Thilsing-Hansen et al, 2002;Roche et al, 2018;Kerwin et al, 2019). However, all studies enrolled a small number of cows, and larger field trials evaluating health and long-term production when using this method of Ca modulation are necessary.…”
Section: Low-calcium Dietsmentioning
confidence: 99%
“…However, all studies enrolled a small number of cows, and larger field trials evaluating health and long-term production when using this method of Ca modulation are necessary. Additional unanswered questions remain regarding the prepartum feeding of zeolite A, including the length of time for which it continues to bind Ca after cessation of feeding, potential interactions with supplemental administration of oral Ca, and the clinical relevance of the concurrent hypophosphatemia and hypomagnesemia seen during and after feeding (Kerwin et al, 2019).…”
Section: Low-calcium Dietsmentioning
confidence: 99%